2019
DOI: 10.1136/rmdopen-2018-000878
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of autoimmune rheumatic diseases on birth outcomes: a population-based study

Abstract: ObjectivesAutoimmune rheumatic diseases (ARDs) affect women of childbearing age and have been associated with adverse birth outcomes. The impact of diseases like ankylosing spondylitis and psoriatic arthritis (PsA) on birth outcomes remains less studied to date. Our objective was to evaluate the impact of ARDs on preterm birth (PTB), congenital anomalies, low birth weight (LBW) and small for gestational age (SGA), in a large cohort of women.MethodsWe conducted a propensity score-matched analysis to predict ARD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
4
23
1
Order By: Relevance
“…Strengths of this study include the large sample created from birth records and hospital discharge summaries. This birth cohort has been used by other researchers to estimate associations between maternal conditions and pregnancy outcomes (2,34,35). By relying on a large, administrative database, we were able to quantify mediated pathways of relatively rare complications, with further stratification by race/ethnicity to improve generalizability to specific populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Strengths of this study include the large sample created from birth records and hospital discharge summaries. This birth cohort has been used by other researchers to estimate associations between maternal conditions and pregnancy outcomes (2,34,35). By relying on a large, administrative database, we were able to quantify mediated pathways of relatively rare complications, with further stratification by race/ethnicity to improve generalizability to specific populations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, these select autoimmune conditions were chosen based on frequency of occurrence and reported increased risk with adverse pregnancy outcomes. Exposures that occurred with less frequency in our sample (e.g., psoriatic arthritis [n = 116] [2] or ankylosing spondylitis [n = 128] [2]) could not be estimated with a mediation analysis but should be pursued in other data sets with more exposures. Likewise, we were only able to assess pregnancy complications that are coded in discharge summaries and occur with enough frequency to investigate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than pathogens, a common pathway through maternal immune activation (MIA) could in part be the link between maternal infections during pregnancy and neuropsychiatric disorders in the offspring. Case-control studies and meta-analyses have shown that maternal autoimmune disorders are associated with ASD and developmental delay [12][13][14][15][16][17] . One case-control study indicated asthma and allergy to be significantly associated with ASD 18 .…”
Section: Discussionmentioning
confidence: 99%